2008
DOI: 10.1177/030802260807100205
|View full text |Cite
|
Sign up to set email alerts
|

Social Services Occupational Therapists' View of Practice and Integration with Health: A Survey

Abstract: There is little known about social services occupational therapy provision within Scotland and England. This information is important when planning strategically for the future. The aim of this study was to understand the views of social services occupational therapists on their practice and integration with health services. Systematic random sampling of social work/social services departments was completed (n = 10) and 57 occupational therapists within these departments received a mailed questionnaire. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 19 publications
0
21
3
Order By: Relevance
“…Counter to Mackie and Darvill's (2016) findings of six key areas required for integration, this study suggests a focus is required on three factors: leadership, communication and joint education need to be prioritised to avoid being overly side-lined by other potential time-consuming process areas (Figure 2) that need attention, but not at the expense of the essential enablers. Forsyth and Hamilton (2008) identify many practical aspects, such as budgets and resources, as potential obstacles for integration. No evidence was apparent in this study to support Forsyth and Hamilton's (2008) findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Counter to Mackie and Darvill's (2016) findings of six key areas required for integration, this study suggests a focus is required on three factors: leadership, communication and joint education need to be prioritised to avoid being overly side-lined by other potential time-consuming process areas (Figure 2) that need attention, but not at the expense of the essential enablers. Forsyth and Hamilton (2008) identify many practical aspects, such as budgets and resources, as potential obstacles for integration. No evidence was apparent in this study to support Forsyth and Hamilton's (2008) findings.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the integration of occupational therapy services are sparse. Donnelly et al (2013) explored the integration of occupational therapy into primary care, while Forsyth and Hamilton (2008) examined a social services occupational therapist's views on integrating with health. Donnelly et al's (2013) Canadian study employed four case studies and explored the interprofessional team's view of occupational therapists integrating into primary care.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It is further suggested that people's experience of the process and satisfaction with the home modification would improve if occupational therapists had a greater understanding of their role [ 20 , 22 , 23 ], and the lack of available guidance and standardised assessment tools is seen as a contributing factor [ 16 , 21 , 22 , 24 ]. This issue is further exacerbated by a lack of design and construction knowledge [ 8 , 20 , 25 ], leading to occupational therapists making the assumption that the modification process is simple [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…This issue is further exacerbated by a lack of design and construction knowledge [ 8 , 20 , 25 ], leading to occupational therapists making the assumption that the modification process is simple [ 26 ]. Interestingly, evidence suggests that occupational therapists want a more standardised approach to the whole modification process [ 21 ] and that the profession should consider ways to amalgamate the occupational therapy process into the wider design and construction process [ 22 , 23 , 27 ]. Thus, given that occupational therapists use the principles of design and construction in interventions involving modifying the home environment in their everyday practice, the aim of this study was to develop an occupational therapy design and construction protocol for modifying home environments.…”
Section: Introductionmentioning
confidence: 99%